Near field wireless power transfer system - Goh, Brenton Zheng Hong (Nanyang Technological University, 2023)
A developing technology called wireless power transfer (WPT) makes it possible to transmit electrical energy without the usage of physical conductors. Due to its potential to completely change how we power remote electrical devices and systems, this technology has attracted a lot of attention. The project entails designing and constructing a WPT system that can wirelessly transmit electricity from a source coil to a receiver coil that is cm in size and located beneath the human skin. For this project, we used simulation and verified formulas to estimate to fine-tune an inductive link, resulting in a PTE of 88% at 4mm and an efficiency of 52% at 20mm. When a skin model was inserted between the two coils, a small decrease in PTE was seen. An additional strategically constructed ferrite core was installed for the Rx coil to improve the PTE of the WPT. Aluminium plates are used to prevent radiation from radiating in an undesirable direction, while ferrite substrates are used to shield EMI from magnetic material in the surrounding environment, including the aluminium plates. Finally, a physical model was constructed to verify the simulation results and shows an agreeable result when compared with the simulation results.